Legal Protection Reform for Notaries Regarding Time Limits on Authority - Yuswanti, Adillah; Santiago, Faisal (Journal of Comprehensive Science, 2024)
This research examines the legal protection for notaries in Indonesia, particularly concerning the legal vacuum that arises in the context of the time limits on notary authority. Although notaries play a vital role as public officials who authenticate authentic deeds, existing regulations, including the Notary Position Law (UUJN), still contain gaps that threaten the integrity of this profession. This study highlights the urgency of reforming legal protection for notaries by identifying unclear provisions and providing concrete recommendations to strengthen legal protection. By analyzing the implications of legal vacuums on public trust and professional integrity, this research aims to offer effective solutions to enhance legal protection for notaries and strengthen their position within the Indonesian legal system.